Wedge strategies, Japan-ASEAN cooperation, and the making of EAS: implications for Indo-Pacific institutionalization - Koga, Kei (University of Michigan Press, 2022)
I argue that it is difficult for ASEAN’s cooperation with Japan and other external powers to expand in geographic scope from Southeast Asia to the Indo-Pacific because of the availability of wedge strategies. A wedge strategy refers to “a state’s attempt to prevent, break up, or weaken a threatening or blocking alliance at an acceptable cost.” Multilateral institutions are susceptible to a wedge strategy by major powers that seek to prevent each other from gaining more influence over the institution. An institution is even more vulnerable if its decision-making mechanism is consensus-based as in ASEAN, and this remains the case even if a norm like ASEAN centrality becomes an institutional principle. Wedge strategies make it less likely that an effective Indo-Pacific regional institution based on ASEAN will be established. The importance of wedge strategies in the development of regional institutions is evident in one institution that experienced geopolitical competition between Japan and China during its establishment—the East Asia Summit (EAS). This is a unique institution for multiple reasons. First, it does not have “ASEAN” in the institutional name, unlike the ARF, ASEAN+3 and ADMM-Plus. Second, its geographical scope goes beyond Southeast Asia, focusing on East Asia—the combination of Northeast Asia and Southeast Asia. Third, it was not initially based on the assumption that ASEAN would play the central role unlike other ASEAN-led institutions. Admittedly, EAS eventually became an ASEAN-led institution that values ASEAN centrality. However, EAS had the potential to be a different type of regional institution—one led more decisively by China—if ASEAN was not the primary player in shaping its agendas and functions. In this sense, the establishment process of EAS is worth exploring in order to deepen the understanding of ASEAN’s cooperation with external powers beyond Southeast Asia, particularly in the Indo-Pacific region.